Relações executivo-legislativo e presidencialismo: elementos teóricos aplicados à analise da agenda econômica presidencial no Brasil (1995-2006) - Leite Neto, Fernando Ribeiro (2010)
The study intends to identify the institutional relationships among between the executive and legislative branches in the Brazilian coalition presidentialism. The analysis lays its focus on the economic agenda carried on by Fernando Henrique Cardoso in his two mandates (1995-2002) and Lula s first mandate (2003-2006). It is understood that economic agenda can be addressed by Ordinary and Complementary Bills claimed by the executive and approved in the Chamber of Deputies. First of all, the thesis deals with the generic institutional relations among executive and legislative branches within presidential governments (Chapters 1 and 2). After analyzing the institutional and political framework of Brazilian coalition presidentialism (Chapter 3), the study presents the institutional and political dynamics related to the process of executive bills at the Chamber of Deputies. The intention is to address economic agenda s political and institutional features (Chapter 4)